The Tit & the Moon - Luna, Bigas; Alcaine, José L.; Durán, Biel; May, Mathilda; Darmon, Gérard (Tartan Video, 2005)
Tete is a nine year old boy who is consumed with jealousy at his baby brother′s monopoly of his mum′s nipples. After asking the moon for a breast of his own, his prayers are answered with the arrival of Estrellita (Mathilda May), a beautiful French dancer. But the course of true love doesn′t run smooth and Tete finds stiff competition for her affection. She is deeply in love with her cabaret partner, Maurice, the flatulent motorbike rider, and is also being pursued by Miguel, the hunky flamenco-singing teenager. A sexy, surreal fairytale, "The Tit & the Moon" is another memorable offering from Spain′s most colourful director. [www.palisadestartan.com]